Ketuntasan Belajar Matematika Siswa Sekolah Dasar Melalui Pendekatan Realistik - Resa Nurlita; Puput Wahyu Hidayat; Iri Hamzah (JURNAL KEILMUAN TEKNOLOGI DAN PENDIDIKAN TERPADU, 2026)
This research aims to improve the learning process and outcomes of Mathematics of flat building materials in grade V students of SDN 60/II Muara Bungo through the application of the Realistic Mathematics Education (RME) model. Preliminary observations show conventional teacher-centered learning with low levels of student engagement and learning outcomes; Only 18.18% of students achieved completeness. This class action research is carried out in two cycles, where each cycle consists of planning, implementation, observation, and reflection.  The results showed a significant increase in educators' activities from the "Good" to "Very Good" category (75% to 100%), as well as an increase in student learning activities from 59% to 81%. This improvement in the learning process is positively correlated with learning outcomes; The percentage of student learning completeness increased from 72.73% in Cycle I to 77.27% in Cycle II, exceeding the success indicator of 75%. These findings confirm that RME is effective in encouraging active, meaningful, and student-centered Mathematics learning, as well as relevant to the implementation of the Independent Curriculum.   Keywords: Mathematics Learning; Flat Build Tour; Classroom Action Research; Realistic Approach